Impact of Family Separation on Subjective Time Pressure and Mental Health in Refugees from the Middle East and Africa Resettled in North Rhine-Westphalia, Germany: A Cross-Sectional Study - Matthias Hans Belau (MDPI AG, 2021)
Little is known about social determinants among refugees resettled in Germany. This study aims to examine the impact of family separation on refugees’ subjective time pressure and mental health. Data come from the FlueGe Health Study (n = 208), a cross-sectional study administered by Bielefeld University. We used logistic regression analysis to investigate the effect of family separation on (i) being time-stressed and (ii) having a high risk for adverse mental health, considering sociodemographic and postmigration factors. As a result, more than 30% of participants with a spouse or partner and about 18% with a child or children reported separation. Multiple logistic regression showed that family separation was not associated with being time-stressed, but separation from at least one child was associated with adverse mental health (OR = 3.53, 95% CI = [1.23, 10.11]). In conclusion, family separation primarily contributes to adverse mental health among refugees from the Middle East and Africa resettled in North Rhine-Westphalia, Germany. Therefore, policies and practices that facilitate family reunification can contribute significantly to the promotion of refugees’ mental health and well-being.